Crystal-Structure Simulation of Methylthiolated Peri-Condensed Polycyclic Aromatic Hydrocarbons for Identifying Promising Molecular Semiconductors Discovery of 1,3,8,10-tetrakis(methylthio)peropyrene Showing Ultrahigh Mobility - Bulgarevich, Kirill (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.